Analisis Komparatif Metode EOQ, POQ, dan JIT dalam Pengendalian Persediaan - A Dandi Setiawan; Ayudyah Eka Apsari (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Inventory management plays a crucial role in supporting operational continuity by ensuring raw material availability while maintaining cost efficiency. UMKM Es Teh Kampoeng Solo utilizes a centralized warehouse to supply raw materials to multiple outlets. Nevertheless, procurement decisions are predominantly based on managerial experience and routine practices, which may lead to excess inventory or stock shortages. This study was conducted to evaluate the effectiveness of three inventory control approaches, namely Economic Order Quantity (EOQ), Periodic Order Quantity (POQ), and Just In Time (JIT), in identifying the most efficient inventory management method. A quantitative case-study design was employed using primary and secondary data obtained through observations, interviews, documentation, and company records from January to April 2026. The materials examined included tea, sugar, cups, ice blocks, 3 kg LPG cylinders, straws, and plastic packaging. The findings indicate that EOQ provides the lowest inventory cost, amounting to Rp1,157,818, compared with the existing system at Rp2,255,782, POQ at Rp5,553,572, and JIT at Rp5,111,040. Furthermore, EOQ reduced inventory expenses by 48.67% relative to the current practice and generated safety stock as well as reorder point values that support more systematic inventory planning. Based on these results, EOQ is considered the most suitable method for inventory control at UMKM Es Teh Kampoeng Solo because it offers the greatest cost efficiency, minimizes stockout risk, and can be implemented more easily than the alternative methods.